First record of Hyalochiton komaroffii in Slovenia (Heteroptera: Tingidae) - Kunz, Gernot (Acta entomologica slovenica (Ljubljana), 2009)
The tingid Hyalochiton komaroffii (Jakovlev, 1880) was found in Slovenia for the first time.
Keywords: entomologija; favna; nove vrste; Slovenia; Slovenija; stenice